An assessment of drinking water quality in parts of Skudai, Johor Bahru - Othman, Abd. Rasid; Mohd. Nor, Mohd. Asri; Aris, Azmi; Teng, Keat Hui; Jora Singh, Jagjit Singh (Penerbit UTM Press, 1992)
In a assessment of drinking water quality in Skudai Johor Bahru, piped water samples in the distribution system from three different standpipe locations in Taman Sri Skudai, Taman Sri Pulai and Universiti Teknologi Malaysia (UTM) campus were collected and tested for selected ions and bacteriological quality. The result show that pipe water supplied from a treatment plant at Gunung Pulai in Pontian was low in mineral content. No Eschericia Coli were detected expected at the UTM Campus with concentration of 3 counts/100 mL in one out of 12 sample tested. Total coliforms were found at each site with concentration ranging from 1 to 13 counts/100 mL in 15 out of 6 samples. Except for the coliforms and the fluoride levels exceeding a little over 1.5 mg/L in 8% of the samples, drinking water in the distribution system in the study area can generally be said to have met the World Health Organization (WHO) guidelines during the study period. However, with the detection of coliforms and E. Coli at the household standpipes, the possibility of the distribution system in Skudai having pathogen contamination from time to time cannot be dismissed.